Pemberdayaan Karyawati Pabrik Tempe Membuat Pupuk dari Limbah Cair untuk Budidaya Sayur Sehat - Agung Astuti; Sarjiyah Sarjiyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The production of tempe by AULIA has created a new problem of smelly liquid waste. This problem may be overcome by converting the waste to organic liquid fertilizer for healthy vegetable cultivation. In this project, the women employee of AULIA tempe producer were trained in a program to utilize tempe liquid waste for healthy vegetable cultivation. The objective of this project was to improve their awareness of the environmental problem and convert such waste for healthy vegetable production. The activities during the training included counseling, training, and assistance in the production of activators, healthy vegetable cultivation by utilizing organic liquid fertilizer made of tempe liquid waste. The training was evaluated by conducting pre-and post-test to view the trainee's capability in absorbing the training program. Following the training, the trainee demonstrated their ability to absorb the training program as evidenced by their improved knowledge of the use of liquid organic waste (POC) by 34.4% and enhanced skill of organic liquid fertilizer and healthy vegetable cultivation by 66.7%. The result of the training program was the production of an organic liquid fertilizer marked as POCUMY. It was also found that POCUMY increased the show's healthy appearance of collards, chili, tomato, and eggplant. The training program conducted in this project has undoubtedly improved the trainee's skill in producing organic liquid waste and its use as a fertilizer for vegetable cultivation for family consumption.